Evaluasi Kesiapan Kerangka Kerja Keamanan Informasi Pada Dinas Komunikasi dan Informatika Kota Batu Dengan Menggunakan Indeks KAMI - Shella Indah Dwi Octaviani; Suprapto Suprapto; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the Batu City Government there is one office that is engaged in communication and informatics and provides public services, namely the Department of Communication and Informatics. Department of Communication and Informatics of Batu City requires an evaluation of information security. As an information provider, the Department of Communication and Informatics of Batu City requires an evaluation of the level of information security. In this study evaluation was conducted with a questionnaire instrument based on the Information Security Index (KAMI) to see the results of the completeness and maturity of information security in 5 areas, governance, risk management, frameworks, asset management, and technology. From the evaluation results, it is known that for completeness levels get a score of 203 and the average maturity level of each information security area is at Level I to level I +. This states that the Department of Communication and Informatics of Batu City was declared not feasible to carry out ISO 27001 certification. Recommendations were obtained from the results of comparisons between Index of Information Security and controls of ISO 27001. One recommendation that could be given to the Batu Communication and Information Office was to make a policy for information security base on objective control A.5.1 in ISO 27001.